Análisis ambiental del capital físico de la PACAT en la provincia de Tungurahua en el periodo 2021-2022. - Ramírez Moya, María José (2022)
This research study evaluates the farms of PACAT associates, considering ten agroecological components and 80 indicators, built with the active participation of its partners. To categorize the farms, the MESMIS methodology was used, in three sustainability indices, category A (sustainable), category B (moderately sustainable), and category C (unsustainable). In the 92 farms surveyed in the three zones, the final results show that they have made significant progress in most of the agroecological components with an average score in the high zone of 73.3 points, in the middle zone of 73.1 and the low zone of 74.7, which means that the farms of the producers associated with PACAT, carry out agroecological practices within their farms, placing them in category B (moderately sustainable); that is, they have begun to put into practice several of the agroecological recommendations, and some progress and achievements have been observed. Finally, comparisons were made between the zones with the ten components, and sustainability radial diagrams were constructed. In these, the potentialities and limitations of each component of the agroecological farms of the zones are visualized.